The principal's guide to curriculum leadership - Sorenson, Richard D.; Goldsmith, Lloyd Milton; Mendez, Zulma Y.; Maxwell, Karen Taylor (Thousand Oaks, California : Corwin, 2016)
This guide walks headteachers through the curriculum development and renewal process with a focus on integrating standards. Includes case studies, activities, and curriculum models.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 22, 2016).
Keywords: Curriculum planning; Educational leadership